Synthesis of Hydroxyapatite with Antibacterial Properties Using a Microwave-Assisted Combustion Method - Suphatchaya Lamkhao (2019)
© 2019, The Author(s). The prevention of implant-associated infections has been increasing clinically in orthopedic surgery. Hydroxyapatite with antibacterial properties was synthesized using a microwave-assisted combustion method. High crystallinity at low temperature can be achieved using this method. The synthesized hydroxyapatite exhibited a superior clear zone for both Gram-positive and Gram-negative bacteria. Electron spin resonance (ESR) and X-ray photoelectron spectroscopy (XPS) were used for the radical investigation. The application of intelligent ink testing and an antioxidant assay using DPPH reduction were also used to confirm the existence of radicals. These techniques provided data confirming that radicals are responsible for the antibacterial properties. The synthesized antibacterial hydroxyapatite would be a good candidate for the prevention any infection with medical implants and injection materials causing failure in bone repair.